AFLIBERCEPT AFTER RANIBIZUMAB INTRAVITREAL INJECTIONS IN EXUDATIVE AGE–RELATED MACULAR DEGENERATION: The ARI2 Study. Issue 12 (December 2018) - Blanco-Garavito, Rocio; Jung, Camille; Uzzan, Joel; Quaranta-ElMaftouhi, Maddalena; Coscas, Florence; Sahel, Jose; Korobelnik, Jean-Francois; Béchet, Stéphane; Querques, Giuseppe; Souied, Eric H.
Abstract : Purpose: To analyze the efficacy of aflibercept switch treatment for regression of pigment epithelial detachment (PED) in patients previously treated with ranibizumab. Methods: Multicenter, prospective, nonrandomized clinical trial. One eye of patients presenting neovascular age–related macular degeneration with PED of more than 250 μ m in height, with persistent fluid, was included. Patients had to have received at least six ranibizumab intravitreal injections during the 12 months before enrollment. Patients were switched from ranibizumab pro re nata to aflibercept (fixed regimen, 3 monthly intravitreal injections, and then Q6). Main outcome measure was change in PED height from baseline to Week 12 after switch. Secondary outcomes were best-corrected visual acuity and PED volume changes. Results: Eighty four patients were included. Mean delay between last ranibizumab intravitreal injection and switch was 44.7 days. Mean maximal PED height at baseline visit was 347 μ m (±109) and reduced to a mean of 266 μ m (±114) at Week 12 ( P < 0.001) and 288.2 μ m at Week 32 ( P < 0.001). Mean PED volume was reduced from 1.3 mm 3 to 0.98 mm 3 at Week 12 ( P < 0.001). Best-corrected visual acuity improved by 3.3 Early Treatment Diabetic Retinopathy Study letters at Week 32 ( P = 0.003). Conclusion: Aflibercept switch therapy seems to be effective on large PED in patients previously treated with pro re nata ranibizumab. Abstract : Treatment-resistant pigment epithelial detachments can be effectively treated with aflibercept switch therapy. Patients were treated with 3 monthly intravitreal injections and then a Q6 regimen. Mean pigment epithelial detachment height and volume were statistically reduced after the switch at primary endpoint (12 weeks), and best-corrected visual acuity also improved steadily throughout the duration of the study.